Development of Interactive E-book on Energy Resources to Enhance Student’s Critical Thinking Ability - Hasan, Muhammad Fikri; Suyatna, Agus; Suana, Wayan (Universitas Islam Negeri Raden Intan Lampung, 2018)
This research aimed to develop a valid interactive e-book using Learning Content Development System (LCDS) with scientific approach on energy resources to enhance student’s critical thinking ability, to know readability and the ease of operating the developed e-book. The method used is research and development. The implementation of procedures adopted from Sugiyono’s design which consisted of 7 adjusted steps that were potency and problem assessment, data collecting, developing preliminary form of product, expert validation, design revision, one-on-one test, and product revision. Developed e-book contains pictures, animations, simulations, learning video, essay question, and interactive test. The e-book has been validated in content and design with results “very appropriate” in quality and “proper to use” as the recommendation for students in learning energy resource topic with scientific approach to foster critical thinking ability. One-on-one test’s results show that e-book is very easy to operate with score 3,68 and has very good readability with score 3,60.